Kaleidoscope. - Tolstaya, Katya (Brill's series in church history., 2013)
Theological hermeneutics receives a new impulse in this book through critical investigation of F.M. Dostoevsky's personal faith in its correlation both to his literary oeuvre and to its reception by the two main representatives of dialectical theology, K. Barth and E. Thurneysen.